Surface Plasmons: Propagating and Localized Surface Plasmons in Hierarchical Metallic Structures for Surface‐Enhanced Raman Scattering (Small 11/2013). Issue 11 (3rd June 2013) - Wang, Xinnan; Wang, Yuyang; Cong, Ming; Li, Haibo; Gu, Yuejiao; Lombardi, John R.; Xu, Shuping; Xu, Weiqing
<x xml:space="preserve">Abstract</x> A highly ordered hierarchical periodic structure with a large area is fabricated to support surface plasmon (SP) and surface‐enhanced Raman scattering (SERS). This novel metallic submicro‐nano structure described on page 1895 exhibits a complex honeycomb‐like geometry, which is confirmed in experiments to support both PSPs and LSPs. Multiple modes of SPs are expected to have co‐enhanced Raman scattering, heralding a further development of more sophisticated hybrid surface plasmonic nanodevices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>